(untitled) - O’Leary, Timothy J. (Boston, 2004)
Computing Today was developed and written to stimulate student learning. Students will be actively engaged by its unique, visual orientation that includes numerous screen shots and steps on ‘how to.’ Additionally, various integrated exercises and activities will allow for optimum reinforcement. Current topics and technology, such as a Personal Digital Assistant (PDA), are skillfully woven throughout the book to catch students’ interest and motivate them. Computing Today offers students and instructors a great introduction to the world of IT and how it can benefit you. It is written by the best-selling and well- known author team of Timothy and Linda O’Leary, who actively teach today. When bundled with software application lab manuals, students are given a complete representation of the fundamental issues surrounding the personal computing environment.
Keywords: Electronic digital computers